Synthesis and characterization of Ce-doped MoO3nanobelts for using as visible-light-driven photocatalysts - Phattranit Dumrongrojthanath (2018)
© 2018 Elsevier Ltd 0–4 wt% (0–4.11 mol%) Ce-doped MoO3nanobelts were successfully synthesized by hydrothermal method at 180 °C for 20 h. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) show orthorhombic MoO3and Ce-doped MoO3nanobelts with >10 μm long, 200–250 nm wide and their growth along the [010] direction. The photocatalytic performance of pure MoO3and Ce-doped MoO3nanobelts was investigated through photodegradation of methylene blue (MB) under visible radiation. In this research, 3 wt% (3.08 mol%) Ce-doped MoO3nanobelts show the highest photocatalytic performance of 94.84% for degradation of MB induced by xenon visible radiation within 50 min.